Bridging the distributional gap of Tyloridastriata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae) - Kulkarni, Siddharth; Yadav, Swara (Biodiversity data journal, 2015)
Although Tyloridastriata has not been reported from India, observations on India Biodiversity Portal (IBP 2015), an open access repository for biodiversity information of Indian subcontinent, showed images resembling this species. The respective locality in Gujarat, India was explored and specimens were studied to confirm record of T.striata in India. Literature study showed some taxonomic lacunae which needed to be resolved. The tetragnathid spider Tyloridastriata (Thorell, 1877) is redescribed on examination of its long unknown syntypes from Kendari, Southeast Sulawesi deposited in the Natural History Museum of Giacomo Doria, Genoa, Italy and additional material from Kendari and other Indonesian regions. Description of Tyloridastellimicans (Simon, 1885) mentions its identity with T.striata, which however characterizes sub-adult of T.striata and is accordingly synonymized. Tyloridastriata is newly recorded from India which links the distributional gap between China to Australia and Comoros Islands. Distributional and taxonomic records of Tylorida species with T.striata- like globose abdomen infer probable synonymy, which is subject to genus revision.